A Fresh Look at Ethical Perspectives on Artificial Intelligence Applications and their Potential Impacts at Work and on People - Fisher, Eddie John Paul; Fisher, Eddie (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Artificial Intelligence (AI) has recently attracted a heightened interest within the communities of AI theory and practice. Experts in this area have advanced their knowledge and understanding of AI systems and applications and the impact of these on existing technologies in terms of capabilities and benefits/risks. The development of these capabilities has created a different choice that needs to be decided on: let the potential effects of AI grow and become more exciting, at the expense of disturbing ethical concerns and issues, or balance these exciting developments by introducing suitable legislative approaches to address these concerns. The results from this research imply that urgent attention needs to be given to construct primary legislation (acts of Parliament, statutes) and then implement these as a matter of urgency. More focus and attention must be placed on ethical concerns and privacy issues that relate to existing and planned AI developments. It is further suggested that more collaboration and co-operation must be exercised across geographical boundaries between researchers to ensure that the interests of human beings world-wide are considered of paramount importance when developing and rolling out AI systems and applications.